PENGHINDARAN PAJAK, INCOME SMOOTHING DAN NILAI PERUSAHAAN PADA PERUSAHAAN MANUFAKTUR DI INDONESIA - Eko Putra Siburian (Prodi Ilmu Manajemen, Fakultas Ekonomi Universitas Muhammadiyah Cirebon, 2023)
Tax avoidance and income smoothing are important issues that impact the company's operations. The complexity between these two phenomena affects firm value, which is often influenced by family ownership, which influences how manufacturing companies avoid tax avoidance and income smoothing. This study aims to examine the effect of tax avoidance and income smoothing on firm value, with family ownership as a moderating variable. Hypothesis testing was carried out using a multiple regression model with panel data for manufacturing companies listed on the Indonesia Stock Exchange (IDX) for the 2012-2021 period. The results show that tax avoidance has a negative effect on firm value. Tax avoidance is high risk and can reduce company value. This study also found that income smoothing has a positive effect on firm value. Companies tend to do income smoothing to meet market expectations and get benefits in the form of lower debt costs. In addition, this study shows that family ownership strengthens the negative effect of tax avoidance on firm value. However, this study did not find any moderating effect of family ownership on the effect of income smoothing on firm value. Keywords: Firm Value, Tax, Income Smoothing